2017
DOI: 10.3390/coatings8010007
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Friction of Silicon Surfaces Using Nanopatterns at the Nanoscale

Abstract: Friction and wear become significant at small scale lengths, particularly in MEMS/NEMS. Nanopatterns are regarded as a potential approach to solve these problems. In this paper, we investigated the friction behavior of nanopatterned silicon surfaces with a periodical rectangular groove array in dry and wear-less single-asperity contact at the nanoscale using molecular dynamics simulations. The synchronous and periodic oscillations of the normal load and friction force with the sliding distance were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…A series of MD simulations was used to study the frictional behaviour of nanopatterned silicon surfaces and how nanopatterning can be used to tune friction at the nanoscale. 135 It was found that for nanopatterned surfaces, there is always a linear dependence of load on the frictional forces, both for adhesive and non-adhesive surfaces, which is independent of the nanopattern geometry. This can represent Amontons' law (eqn (1)) and it's relation to the real contact area.…”
Section: Molecular Dynamics Simulations Complementing Ffmmentioning
confidence: 99%
“…A series of MD simulations was used to study the frictional behaviour of nanopatterned silicon surfaces and how nanopatterning can be used to tune friction at the nanoscale. 135 It was found that for nanopatterned surfaces, there is always a linear dependence of load on the frictional forces, both for adhesive and non-adhesive surfaces, which is independent of the nanopattern geometry. This can represent Amontons' law (eqn (1)) and it's relation to the real contact area.…”
Section: Molecular Dynamics Simulations Complementing Ffmmentioning
confidence: 99%
“…Second, micro/nano patterns can efficiently reduce the actual contact area, therefore also reduce the friction efficiency and wear rate. However, the current understanding of the friction behavior on micro/nano textured surface is not sufficient [130]. One reason is the lack of precise tools to study nanoscale friction.…”
Section: Micro-nano Patternsmentioning
confidence: 99%
“…Triboactive surfaces stand for surfaces with controlled frictional behaviour finely tuned in real time by using external stimuli as temperature [9,10], laser beam [11], UV or IR beams [12,13], electric or electrostatic fields [14,15] and many other ways [16,17]. For instance, photo-and thermo-activated self-assembled monolayers (SAM) seem to be a promising way for this purpose [9,10,11,12,13] assuming that suitable functional groups can be found or synthesized for each given application.…”
Section: Introductionmentioning
confidence: 99%